Sentidos constituídos na educação em tempo integral - Soares, Thais Peluzo Abreu Faleiros (2012)
This study aims to develop an understanding of the subjective dimensions of teaching in a full-time school, taking into account the subjective aspects created by those directly involved in this context. It is through their words that we analyze the elements that comprise the meanings (senses) of full-time school models. The theoretical and methodological framework used to support these arguments is socio-historical psychology, which is the constitution of the human phenomena in a social-historical process. To this end, making is active social and historically. The research has two participating subjects, via semi-structured interviews, a teacher and a pedagogical director in a full-time elementary public school, from the city of Palmas, state of Tocantins. The analysis of the interview led to the construction of core elements, manifesting the meaning created by the interviewed parties